The guide to getting paid : weed out bad paying customers, collect on past due balances, and avoid bad debt - Dunn, Michelle A. (John Wiley & Sons, 2011)
Give your business a successful credit and collections plan with this easy and clear guide Over 100,000 businesses have slow or non-paying customers. Yet very few actually have a workable plan for claiming the missing revenue that results. This book gives you a complete solution and tool set to ensure your business maximizes its collections while maintaining an effective, profitable credit plan. You'll discover how to set up an efficient in-house credit policy that not only lets you collect more debts, but also boost sales, increase cash flow, and grow profits. Step-by-step credit management i.